Validity of Enzyme-Linked Immunosorbent Assay (ELISA) as a correlate of protection of meningococcal C conjugated vaccine in adolescents with HIV infection - Daniela Vinhas Bertolini; Luciana Scarlazzari Costa; Bruno Stuart de Castro; Tadeu Pernichelli; Inneke Marie van der Heijden; Silvia Figueiredo Costa; Helena Keiko Sato; Heloísa Helena de Sousa Marques (Journal of Vaccines and Immunology - Peertechz Publications, 2020)
The immunological response to meningococcal C conjugated vaccine can be evaluated by two different tests: the serum bactericidal antibody assay (SBA), which evaluates the qualitative bactericidal capacity of the antibodies, and the Enzyme-Linked Immunosorbent Assay (ELISA), which quantifies the specific serogroup C meningococcal immunoglobulin-G. Incompatibilities between the results of both tests have been reported. Technically, ELISA is simpler, safer, and easier to reproduce when compared to the SBA; thus, an assessment of the validity of ELISA as a protective correlate compared to the SBA gold standard should be performed. This study tested the validity of ELISA for the evaluation of the protective response to the C meningococcal conjugate vaccine in adolescents with HIV compared with the gold standard SBA, to evaluate the reliability of ELISA to infer the protection of the individual.  Blood samples of 92 individuals were analyzed (43 HIV+ and 49 HIV−). We observed a positive intraclass correlation coefficient between the ELISA and SBA responses for HIV+ after vaccination (ricc=0.97; 95% CI, 0.91 to 0.99), and for HIV− before vaccination (ricc=0.98; 95% CI, 0.95 to 0.99). In the HIV+ group, the sensitivity and specificity were both 100% for SBA, and 93.5% and 91.6%, respectively, for ELISA. The observed concordance between the tests suggests that in the HIV+ group the measures of antibodies by ELISA could be extrapolated to predict an individual's protection, suggesting ELISA's reliability. Until now, ELISA was unable substitute the gold standard SBA. Further studies are necessary to reproduce our findings.